Serum Oxidative Status in People with Obesity: Relation to Tissue Losses, Glucose Levels, and Weight Reduction - Beata Szlachta; Anna Birková; Tomasz Wielkoszyński; Alicja Gospodarczyk; Beáta Hubková; Maria Dydoń; Jolanta Zalejska-Fiolka (Antioxidants, 2023)
Background: This work aims to study the effect of reductions in various body mass components on the oxidative, glycemic, and lipid parameters of people with obesity (PWO). Methods: A total of 53 PWO underwent a six-month individualized low-calorie diet combined with moderate exercise, during which anthropometric, biochemical, and oxidative parameters were measured. Probands were divided into groups based on weight, visceral fat area (VFA), total body water (TBW), and skeletal muscle mass (SMM) losses. Results: Weight reduction normalizes glycemia, but VFA reduction is less pronounced, while SMM and TBW reductions are more pronounced in patients with higher initial concentrations of glucose and fructosamine. Moreover, changes in oxidative parameters correlate with changes in glucose. Conclusions: Weight loss, regardless of the reduced tissue, decreases cardiovascular risk. We observed a significant change in almost all parameters related to the redox state. In general, parameters responsible for antioxidant action improved, and markers of oxidative damage decreased. Malondialdehyde, lipid peroxides, and total oxidative status levels can be considered biomarkers reflecting only the current severity of reactive oxygen species genesis processes. When considering the glycemic state, the results are not as clear due to the substantial differences between normoglycemic and hyperglycemic patients. Glycemic status is a factor playing a crucial role in weight reduction.